The Usefulness of Diffusion Tensor Tractography in Diagnosing Neuropathic Pain: A Narrative Review - Yang, Seoyon; Kwon, SuYeon; Chang, Min Cheol (Frontiers in Neuroscience, 2021)
Diffusion tensor tractography (DTT) is derived from diffusion tensor imaging. It has allowed visualization and estimation of neural tract injury, which may be associated with the pathogenesis of neuropathic pain (NP). The aim of the present study was to review DTT studies that demonstrated the relationship between neural injuries and NP and to describe the potential use of DTT in the evaluation of neural injuries that are involved in the pathophysiological process of NP. A PubMed search was conducted for articles published until July 3, 2020, which used DTT to investigate the association between neural injuries and NP. The key search phrase for identifying potentially relevant articles was (diffusion tensor tractography AND pain). The following inclusion criteria were applied for article selection: (1) studies involving patients with NP and (2) studies in which DTT was applied for the evaluation of NP. Review articles were excluded. Altogether, 108 potentially relevant articles were identified. After reading the titles and abstracts and assessment of eligibility based on the full-text articles, 46 publications were finally included in our review. The results of the included studies suggested that DTT may be beneficial in identifying the pathophysiological mechanism of NP of various origins including central pain caused by brain injuries, trigeminal neuralgia, sciatica, and some types of headache. Further studies are needed to validate the efficacy of DTT in investigating the pathophysiology of other types of NP.